Tamil Nadu Development Report - Planning Commission (Planning Commission, 2002)
Tamil Nadu like the other southern states could be classified as a middle-income state among the 14 largest states in India. Since the growth rate in the nineties (1990-91 to 1996-97) has been high (5.2 per cent) it could graduate to the high income category. In terms of per capita income it already stands fifth following Maharashtra, Punjab, Haryana and Gujarat. After relatively slow economic growth in the seventies, Tamil Nadu began to grow at the rate of 5 per cent in the eighties at 6 per cent in the early nineties and nearly 7 per cent in the latter half of the nineties.
Planning Commission Government of India
Planning Commission Government of India